Endoscopic ultrasound in patients with normal liver blood tests and unexplained dilatation of common bile duct and or pancreatic duct. (April 2014) - Oppong, Kofi W.; Mitra, Vikramjit; Scott, John; Anderson, Kirsty; Charnley, Richard M.; Bonnington, Stuart; Jaques, Bryon; White, Steven; French, Jeremy J.; Manas, Derek M.; Sen, Gourab; Nayar, Manu K.
Abstract Objective. To determine the yield of endoscopic ultrasound (EUS) in the investigation of patients with normal liver function tests (LFTs) and unexplained dilatation of common bile duct (CBD) and/or pancreatic duct (PD), following CT and/or magnetic resonance cholangiopancreatography. Materials and methods. Consecutive patients undergoing linear EUS between January 2007 and August 2011 for the indication of dilated CBD and/or PD, normal LFT, and nondiagnostic cross-sectional imaging formed the study group. The study was performed as a retrospective analysis of prospectively collected data. Results. During the study period, 83 patients (CBD and PD dilatation n = 38, PD dilatation n = 5, CBD dilatation n = 40) met the inclusion criteria and underwent EUS. Five (13.1%) of the CBD and PD groups had a new finding, which in one (2.6%) case was causal. In this group, men were significantly more likely to have a new finding (p = 0.012). Eight (20%) of the CBD group had a new finding, which in seven (17.5%) cases was causal. In the CBD group, cholecystectomy was significantly (p = 0.005) more common in those without a finding. Three (60%) of the PD group had a finding on EUS, all of which were causal, including a case of pancreatic malignancy. Conclusion. There is a significant yield from EUS in individuals with isolated PD dilatation and isolated CBD dilatation. Previous cholecystectomy is significantly associated with a negative EUS in the group with isolated CBD dilatation. The yield in those with CBD and PD dilatation was low and a finding was more likely in males.